A sugarcane smut fungus effector simulates the host endogenous elicitor peptide to suppress plant immunity. Issue 2 (12th November 2021) - Ling, Hui; Fu, Xueqin; Huang, Ning; Zhong, Zaofa; Su, Weihua; Lin, Wenxiong; Cui, Haitao; Que, Youxiong
Summary: The smut fungus Sporisorium scitamineum causes the most prevalent disease on sugarcane. The mechanism of its pathogenesis, especially the functions and host targets of its effector proteins, are unknown. In order to identify putative effectors involving in S. scitamineum infection, a weighted gene co‐expression network analysis was conducted based on the transcriptome profiles of both smut fungus and sugarcane using a customized microarray. A smut effector gene, termed SsPele1, showed strong co‐expression with sugarcane PLANT ELICITOR PEPTIDE RECEPTOR1 ( ScPEPR1 ), which encodes a receptor like kinase for perception of plant elicitor peptide1 (ScPep1). The relationship between SsPele1 and ScPEPR1, and the biological function of SsPele1 were characterized in this study. The SsPele1 C‐terminus contains a plant elicitor peptide‐like motif, by which SsPele1 interacts strongly with ScPEPR1. Strikingly, the perception of ScPep1 on ScPEPR1 is competed by SsPele1 association, leading to the suppression of ScPEPR1‐mediated immune responses. Moreover, the Ustilago maydis effector UmPele1, an ortholog of SsPele1, promotes fungal virulence using the same strategy. This study reveals a novel strategy by which a fungal effector can mimic the plant elicitor peptide to complete its perception and attenuate receptor‐activated immunity.